Impact of Irritable Bowel Syndrome and Body Mass Index on Mental Health - A Prospective Cross Sectional Study - Arvind Bamanikar; Shivam Sharma; Bhumika Vaishnav (Journal of Integrated Health Sciences)
Introduction: Irritable bowel syndrome (IBS) is one of the most common causes of chronic diarrhea. Chronic diarrhea has substantial effect on the physical and mental health (MH) of the patient. Aims: The aim of this study was to evaluate the association between IBS with chronic diarrhea and body mass index (BMI) and effect of severity of symptoms, body weight on MH of patients with IBS. Study Design: A prospective cross-sectional study was performed on patients having diarrhea predominant IBS during September 2017–August 2019. Methods: Ninety-seven patients suffering from IBS-D as diagnosed on the basis of Rome criteria IV had were studied. The severity of symptoms in IBS-D where evaluated according to the IBS-score of symptom-severity. MH was assessed by Patient Health Questionnaire-9 questionnaire. Statistical Analysis: SPSS statistical software was used to analyze the data. ANOVA was used to analyze demographic data. Pearson correlation coefficients were used to analyze linear correlation between demographics, BMI, and MH. Multiple regression test was used in MH analysis with respect to predictive role of BMI. Impact of confounding factors was tested with respect to the gender, age, family status, educational status, severity of the symptoms, and BMI. Results considered statistically significant if P < 0.05. Results: The mean BMI was 23.9 + 5.2 kg/m2. The BMI distribution showed that 59.2% of the IBS patients were of normal weight; 29.8% had BMI more than 25 kg/m2 and 11% had BMI subnormal (P < 0.01). MH was negatively associated with both overweight and severe symptoms of IBS-D; after adjusting for age, gender, marital status, and education. Conclusion: IBS-D patients were significantly overweight or obese which was associated with severe symptoms and impaired MH.